2012
DOI: 10.1123/rsj.36.1.60
|View full text |Cite
|
Sign up to set email alerts
|

University Student Interest and Use of Personal Training Services

Abstract: Personal trainers act as a motivating force for individuals interested in improving health and fitness. Having a knowledgeable and well-trained individual at one's side can help meet personal goals. University students are a relatively healthy demographic, although students can be irregular in terms of their physical activity levels. This study investigated student interest and use of personal trainers to determine new marketing strategies by a university supported personal training program to increase student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…For example, Facebook pages may serve as an advertising tool to engage with consumers and promote upcoming events/programs, through status updates that explain relevant information (e.g., location, time, registration). Scholl, Leen, Alexander, Pike, and Johansen (2012) suggested that campus recreation centers use Facebook to market personal training services, and it is assumed it would be helpful in promoting other recreation services. However, the effectiveness of this marketing strategy is unknown.…”
mentioning
confidence: 99%
“…For example, Facebook pages may serve as an advertising tool to engage with consumers and promote upcoming events/programs, through status updates that explain relevant information (e.g., location, time, registration). Scholl, Leen, Alexander, Pike, and Johansen (2012) suggested that campus recreation centers use Facebook to market personal training services, and it is assumed it would be helpful in promoting other recreation services. However, the effectiveness of this marketing strategy is unknown.…”
mentioning
confidence: 99%
“…De fato, os objetivos dos clientes, apesar de apresentarem certos padrões gerais, manifestam determinadas tendências quando considerados os gêneros masculino e feminino. Nestes casos, os homens buscam o trabalho de personal aparentemente por fatores extrínsecos, na intenção de melhor desempenho esportivo ou alívio de lesões, como dores nas costas (Scholl, Leen, Alexander, Pike & Johansen, 2012). No caso de mulheres, aparentemente a busca ocorre por fatores intrínsecos, relacionados a individualidade, eficácia, eficiência, responsabilidade e motivação (Scholl et al, 2012;Rodrigues & Brandão, 2017).…”
unclassified